The use and context of fiber plants during the middle preceramic: evidence from La Yerba II and III, south coast of Peru - Alday, Camila; García, Maria Angélica; Alarcón, Carmela; Beresford-Jones, David (Frontiers in Environmental Archaeology, 2023)
Bast fiber artifacts from the Pacific coast of South America are among the earliest evidence of fabric manipulation and the foundation of the millennial Andean textile tradition. Recent examinations of plant macro remains and plant fiber artifacts from La Yerba II (7570–6674 cal BP) and La Yerba III (6485–5893 cal BP) sites provide insight into how plant fabric technologies and pre-loom textile traditions unfolded over the Middle Preceramic (or Middle Archaic; 8000–5000 BP) on the south coast of Peru. Using light microscopy and scanning electron microscopy (SEM), we conduct comparative analyses of modern and archaeological plants to assess the taxonomy and morphological distinctions between them to discriminate species. We identify materials from wild-gathered plants in the Cyperaceae, Typhaceae, and Apocynaceae families and show how they were used to make fishing nets, looped bags, mats, and other artifacts. Evidence from tools and cut marks also enabled us to reconstruct parts of the chaîne opératoire of the fiber production. We discuss the significance of plants from wetland and estuarine habitats in the interrelated dimensions of fabric manufacture and food consumption among these coastal hunter-gatherers.